Transmission of contagious epidemics from Makran Coast to Muscat and its Suburbs during 1898 and 1899 AD Historical Documentary Study - القطيطي, منال حمد (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This study tried to highlight one of the key issues related to health affairs in Muscat and its suburbs in the reign of Sultan Faisal bin Turkey (1305-1331 AH/ 1888-1913 AD) which concentrated on spread and transmission of epidemics from Makran Coasts adjacent to Oman because of historical communication that links both regions. We preluded the study with the pillar of geographical proximity, and how this natural advantage was reason for beginning of historical relations between Oman and Makran Coast in the late 1900 Century AD. We moved afterwards to address Government of British India and its role in the matter of keeping the historical documents and correspondences related to epidemics and diseases. This was followed by the matter of Sultan Faisal bin Turki's coming to rule in Oman and the beginning of appearance of epidemics in Muscat and its suburbs during 1898 and 1899 AD in its era. The study concluded its subject by correspondences of health affairs between the British Consulate in Muscat to Government of Sultan Faisal bin Turki during 1898 and 1899 AD.